2017
DOI: 10.1152/ajpendo.00262.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paternal obesity on growth and adiposity of male rat offspring

Abstract: Emerging evidence suggests that paternal obesity plays an important role in offspring health. Our previous work using a rodent model of diet-induced paternal obesity showed that female offspring from high-fat diet (HFD)-fed fathers develop glucose intolerance due to impairment of pancreatic insulin secretion. Here, we focused on the health outcomes of male offspring from HFD-fed fathers. Male Sprague-Dawley rats (3 wk old) were fed control (CD-F0) or HFD (HFD-F0) for 12 wk before mating with control-fed female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 56 publications
3
42
1
Order By: Relevance
“…However, we found that body weight was lower in female adult offspring fathered by rats fed with HFD, which was also reported in male offspring (Lecomte et al . ). Ng et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, we found that body weight was lower in female adult offspring fathered by rats fed with HFD, which was also reported in male offspring (Lecomte et al . ). Ng et al .…”
Section: Discussionmentioning
confidence: 97%
“…The study, led by Ng et al, focused on females and found paternal obesity to induce sustained pancreatic β‐cell dysfunction in the offspring without altering growth or adiposity. More recently, and using a similar murine model, Lecomte et al reported birthweight and growth trajectories of male offspring are dramatically affected by paternal obesity, with lower birthweight, stunted growth and decreased adiposity occurring in association with low levels of GH and IGF1 factor.…”
Section: Discussionmentioning
confidence: 99%
“…Undeniably, the experiences of the developing embryo/foetus are primarily those of the mother; therefore, it is maternal contributions to programming of offspring health that have captivated research efforts. In the United States where ~50% of babies are being born to women with either overweight or obesity, a clear link has been established between maternal obesity at conception and offspring's obesity and cardiometabolic risks across the lifespan. In recent years, however, studies have pointed out that paternal obesity is also contributing to the programming of offspring phenotype, but the results from some of these studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations